Effect of Prophylactic Vaccination with the Membrane-Bound Acid Phosphatase Gene of Leishmania mexicana in the Murine Model of Localized Cutaneous Leishmaniasis - María Angélica Burgos-Reyes; Lidia Baylón-Pacheco; Patricia Espíritu-Gordillo; Silvia Galindo-Gómez; Víctor Tsutsumi; José Luis Rosales-Encina (Journal of Immunology Research)
Leishmaniasis is a disease caused by an intracellular protozoan parasite of the genus Leishmania. Current treatments for leishmaniasis are long, toxic, and expensive and are not available in some endemic regions. Attempts to develop an effective vaccine are feasible, but no vaccine is in active clinical use. In this study, the LmxMBA gene of Leishmania mexicana was selected as a possible vaccine candidate using the reverse vaccinology approach, and the prophylactic effect generated by DNA vaccination with this gene in a murine model of cutaneous leishmaniasis was evaluated. The results showed that prophylactic vaccination with pVAX1::LmxMBA significantly reduced the size of the lesion and the parasitic load on the footpad, compared to the control groups. At a histological level, a smaller number of parasites were evident in the dermis, as well as the absence of connective tissue damage. Mice immunized with plasmid pVAX1::LmxMBA induced immunity characterized by an increase in the IgG2a/IgG1>1 ratio and a higher rate of lymphocyte proliferation. In this study, immunization with the plasmid promoted an improvement in the macroscopic and microscopic clinical manifestations of the experimental infection by L. mexicana, with a T helper 1 response characterized by an IgG2a/IgG1>1 ratio and high lymphoproliferative response. These findings support immunization with the plasmid pVAX1::LmxMBA as a preventive strategy against cutaneous infection of L. mexicana.